Sustainable SAP hydrogels enhance controlled urea release in agriculture - Mazlan, Maizatul Husna Nasuha; Hisham, Alyasofea Nazrul; Kaco, Hatika; Sajab, Mohd Shaiful (Universiti Teknologi MARA, Kedah, 2023)
Hydrogels offer unique advantages in agriculture due to their water-retention properties and ability to swell when in contact with water. This study focused on exploring the slow-release capabilities of Super Absorbent Polymer (SAP) hydrogels, particularly in efficiently absorbing urea fertilizer. The researchers developed a nitrogen-based slow-release fertilizer using urea-impregnated hydrogel structures, analyzed through Fourier Transform Infrared (FTIR) analysis. The findings highlight the potential of hydrogel integration in agriculture as an effective technique for self-planting, especially in modern farming. Hydrogels' gradual nutrient release addresses challenges of nutrient leaching and loss, enhancing nutrient availability for plants. Additionally, their water-retention abilities support proper irrigation and reduce water wastage, promoting sustainable water management. Beyond improved crop growth, hydrogel integration bears implications for community economic management. By potentially increasing crop yields, conserving resources, and reducing input costs, this eco-friendly and economically viable approach can pave the way for more sustainable and productive farming practices.